Kesulitan Siswa Kelas XI IPA SMA Negeri Kota Palangka Raya Tahun Ajaran 2018/2019 Dalam Memahami Hukum-Hukum Gas - Vina Aprilia (FKIP Universitas Palangka Raya, 2020)
Students have difficulty understanding gas laws. The aim of this study was to describe the difficulty of students understanding gas laws in class XI IPA of Public Senior High School Palangka Raya in 2018/2019 academic year. This research is a descriptive study. The subjects in this study were students of class XI Science of Public Senior High School 1, 2, and 3 Palangka Raya with a total of 173 students. Data collected using written tests and interviews. The results showed that students had difficulty in understanding the gas laws which included the concepts of: (1) determining the volume of gas resulting from the gas reaction with the same ratio of gas reactants but the ratio of different reagent gas volumes reached 68.20%; (2) determination of the volume of reaction gas with the same ratio of coefficient and volume of reactant gas reaching 65.89%; (3) determination of the number of molecules, initial pressure, final pressure, initial volume and final volume of a gas from two different conditions using the ideal gas equation each reaching 32.94%; 21.38%; 53.17%; 15.60%; and 74.56%.